Cortical asymmetry: catching an object in free fall Assimetria cortical: apreensão de um objeto em queda livre - Bruna Velasques; Sergio Machado; Cláudio Elidio Portella; Julio Guilherme Silva; Patrícia Terra; Camila Ferreira; Luis Basile; Mauricio Cagy; Roberto Piedade; Pedro Ribeiro (Arquivos de Neuro-Psiquiatria)
The main goal of the present study was to analyze theta asymmetry through quantitative electroencephalography (qEEG) when individuals were exposed to a sequential motor task, i.e. catching a ball. The sample was composed of 23 healthy subjects, male and female, between 25 and 40 years of age. A two-way factor Anova was applied to compare pre and post moments related to the balls' drop and scalp regions (i.e., frontal and parieto-occipital cortices). The first analysis of the frontal region compared electrodes in the left, right and left/right hemispheres combined, with the frontal midline electrode (FZ) included in the analysis. The results showed moment and region main effects. The second analysis compared left versus right hemisphere without the FZ site. The findings demonstrated an interaction effect between moment and region. The first parieto-occipital analysis, comparing left, right and central regions, with PZ included in all regions, showed main effects of moment and region. The second analysis, comparing left, right (without Pz) and central regions strictly demonstrated a region main effect. Thus, we observed an asymmetric pattern in the frontal cortex (i.e., planning and response selection) when the subjects were waiting for the balls' drop. Moreover, the left hemisphere seems to engage differently from the other regions when the central nervous system needs to prepare for a motor action. On the other hand, the parieto-occipital cortex, which is related to attentive processes, demonstrated a more asymmetric activity towards the right region which implies a participation of this area in cognitive strategies in this particular task. Taken together, we concluded that the adopted experimental approach can be useful to explore several others directions combining sensorimotor integration tasks with different pathologies, such as depression, Alzheimer's and Parkinson's diseases. O objetivo do presente experimento foi avaliar medidas de assimetria na banda teta através da electroencefalografia quantitativa (EEGq) durante a realização da atividade motora de apreensão de uma bola em queda livre. A amostra constituiu-se de 23 sujeitos saudáveis de ambos os sexos, faixa etária entre 25 e 40 anos. Anova two-way foi utilizada para comparar os momentos pré e pós relacionados à queda da bola, e às regiões do escalpo (córtex frontal e parieto-occipital). A primeira análise da região frontal comparou eletrodos nos hemisférios esquerdo, direito e esquerdo/direito combinados, incluindo na análise o eletrodo frontal mediano (FZ). O resultado demonstrou um efeito principal para momento e região. A segunda análise comparou os hemisférios direito e esquerdo, sem o eletrodo FZ. Neste achado verificou-se um efeito principal para a interação entre os fatores momento e região. A primeira análise realizada na região parieto-occipital comparou as regiões esquerda, direita e central, com PZ incluídos em todas as áreas, demonstrou efeito principal para momento e região. A segunda análise comparou as regiões esquerda, direita (sem PZ) e central, e verificou-se um efeito principal para região. Tais achados indicaram um padrão de assimetria no córtex frontal (ex., planejamento e seleção de resposta) no momento em que os sujeitos esperavam a queda da bola. Além disso, o hemisfério esquerdo parece engajar-se diferentemente em relação às outras regiões quando o sistema nervoso central necessita se preparar para uma ação motora. Por outro lado, o córtex parieto-occipital, o qual está envolvido com processos de atenção, demonstrou uma maior assimetria no hemisfério direito, o que implica uma participação dessa área em estratégias cognitivas para uma tarefa particular. Então, podemos concluir que o procedimento experimental adotado pode ser utilizado para explorar diferentes direções combinando tarefas de integração sensório-motora com diferentes patologias, tais como depressão, doença de Alzheimer e mal de Parkinson.